INTEGRATION OF MERCHANDISE AND ADVERTISING CREATIVE TO INCREASE THE EFFICIENCY OF THE ENTERPRISE (Development Service Industry Management, 2024)
The article aims to explore new approaches to driving demand and improving brand identity by integrating these two important components of a marketing strategy. The article analyzes how strategic point-of-sale placement (merchandising) can be complemented by effective advertising campaigns that include creative solutions focused on emotional connection with consumers. The use of innovative approaches, such as visual merchandising, interactive elements, augmented reality (AR), and advertising personalization, are important aspects that allow creating a holistic, attractive and user-interactive environment that stimulates demand. The study indicates the importance of a deep understanding of consumer sentiment and behavior. Companies that have managed to effectively combine these elements in one strategy are able not only to increase demand, but also to form a positive and memorable brand image. One example of such brands is Nike and Apple, which successfully apply integrated approaches in their campaigns.The article also draws attention to the changing role of digital technologies in merchandising and advertising. Studying the impact of emerging technologies, such as artificial intelligence (AI) and big data, allows brands to more accurately target their strategies to the needs of specific consumers, thereby increasing the effectiveness of campaigns. Thanks to a comprehensive approach to analyzing the integration of merchandising and advertising creative, the article identifies new opportunities for business in the context of globalization and digitalization of the market. In addition, it provides recommendations for adapting strategies to the changing conditions of the competitive environment, which ensures the sustainability of the brand in the market in the long term. Thus, the article makes a significant contribution to the development of theoretical and practical aspects of modern marketing, providing enterprises with new tools to improve their market position, stimulate demand and build a strong brand identity.
Keywords: merchandising; advertising creative; entrepreneurship; enterprise economy; integration; branding; stimulation of demand; brand identity; marketing strategies